Free radical destruction of hydroxyl-containing amino acids - Sladkova, Anastasia A.; Edimecheva, Irina P.; Sosnovskaya, Anna A.; Shadyro, Oleg I. (Journal of the Belarusian State University. Chemistry, 2019)
А new way of the free radical ROS- and HOCl-induced destruction of serine, threonine, and their peptide derivatives due to the nitrogen-centered radicals formation and their subsequent decomposition with the side chain elimination has been established. It has been shown that substances with reducing properties are inhibitors of this process, while oxygen does not affect the probability of its occurrence. The data obtained are relevant for the development of novel approaches to the search for effective free radical processes regulators.